(untitled) (Journal of Civil Engineering Researchers, 2025)
Conventional steel braces increase the risk of structural damage during earthquakes due to compressive buckling. In this study, the performance of a steel frame equipped with a memory alloy cable brace with a central cylinder is investigated through numerical modeling in ABAQUS. This system is expected to exhibit superior seismic performance compared to traditional braces due to characteristics such as superelasticity, self-centering, and energy dissipation, and to return to its initial state after an earthquake. It can significantly enhance the seismic performance of steel frames with minimal construction interference and reduced construction time. After model validation, this study evaluates the effects of cable type, memory alloy properties, and cable diameter on the lateral performance of the steel frame with central cylinder cable braces. The results indicate that even using steel cables in this system significantly increases strength, stiffness, and energy absorption compared to a frame without braces, although ductility decreases by 25%. Replacing the steel cable with a memory alloy cable simultaneously improves strength, stiffness, energy absorption, and ductility (by 10%) compared to the steel-cable specimen, compensating for the ductility reduction. Furthermore, enhancing the superelastic properties of the memory alloy increases the load-bearing capacity and absorbed energy, while increasing the memory alloy cable diameter (from 6 to 16 mm) improves all performance indicators, especially stiffness and strength, without significant loss of ductility. Overall, the results demonstrate that using memory alloy cables, along with optimizing their properties and diameter, is an effective approach for simultaneously improving strength, stiffness, ductility, energy dissipation, and seismic behavior of structures.